2003
DOI: 10.1177/000348940311200505
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Recurrent Nasopharyngeal Carcinomas with Technetium-99m Methoxyisobutylisonitrile Single Photon Emission Computed Tomography in Patients with Indeterminate Magnetic Resonance Imaging Findings after Radiotherapy

Abstract: The aim of this study was to evaluate the effectiveness of technetium-99m methoxyisobutylisonitrile (Tc-99m MIBI) single photon emission computed tomography (SPECT) for detecting recurrent nasopharyngeal carcinomas (NPCs) when magnetic resonance imaging (MRI) findings are indeterminate. Twenty-eight NPC patients who had received radiotherapy and had indeterminate MRI findings were included in the study. We performed MRI, Tc-99m MIBI SPECT, and biopsy at least 4 months after radiotherapy and within 1 week. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A study of patients with advanced NPC found that a combination of EBV DNA clearance and a reduction in maximum standardized uptake value of less than 50% at 4 weeks after initiation of chemotherapy was prognostic and predicted improvements in PFS and OS compared with either modality alone, which provided an opportunity for modification of treatment decisions at an early stage [64]. The functional aspect of PET allows tissue metabolic changes to be detected that may not be apparent on cross-sectional imaging and has also been found to be more accurate than MRI in the assessment of early treatment response [65]. These studies support a potential opportunity to identify low-risk groups who could potentially be spared from concurrent chemotherapy throughout the treatment course.…”
Section: Imaging As Biomarkermentioning
confidence: 99%
“…A study of patients with advanced NPC found that a combination of EBV DNA clearance and a reduction in maximum standardized uptake value of less than 50% at 4 weeks after initiation of chemotherapy was prognostic and predicted improvements in PFS and OS compared with either modality alone, which provided an opportunity for modification of treatment decisions at an early stage [64]. The functional aspect of PET allows tissue metabolic changes to be detected that may not be apparent on cross-sectional imaging and has also been found to be more accurate than MRI in the assessment of early treatment response [65]. These studies support a potential opportunity to identify low-risk groups who could potentially be spared from concurrent chemotherapy throughout the treatment course.…”
Section: Imaging As Biomarkermentioning
confidence: 99%
“…A noninvasive approach to predicting early response to treatment and thus offering an opportunity for deescalation in NPC is with fluorodeoxyglucose positron emission tomography (PET). The functional aspect of PET allows tissue metabolic changes to be detected that may not be apparent on cross-sectional imaging and has been found to be more accurate than magnetic resonance imaging (MRI) in the assessment of early treatment response . One longitudinal study of serial PET computed tomography imaging of NPC found significant reductions in the maximum standardized uptake value by 71% at the primary site and 77% in nodal disease by the middle to late treatment period (50 Gy of radiation).…”
Section: Introductionmentioning
confidence: 99%
“…Among the radionuclide studies for pharyngeal carcinoma considerable experience has been accrued with Tc 99m methoxyisobutylisonitrile (MIBI), thallium (Tl‐201), and fluorodeoxyglucose (FDG‐18) positron emission tomography (PET) studies of nasopharyngeal carcinoma pre‐ and post‐therapeutically, 5–12 but no studies have been carried out in a Pakistani population. To our knowledge, only one or two studies have been conducted regarding oropharyngeal and hypopharyngeal carcinoma pretherapeutically 1 but no study has explored the role of Tc 99m MIBI in the assessment of treatment response.…”
Section: Introductionmentioning
confidence: 99%